Substantiation of methodical approaches to a unified (complex) norm-setting in hygiene - Sidorenko, G I (Journal of hygiene, epidemiology, microbiology, and immunology, 1976)
Hygienic norm-setting of admissible content of noxious chemical substances separately for atmospheric air, the air in industrial plants, water and food products, does not take into account the possibility of combined intake of these substances into the organism. It is therefore necessary to elaborate methodical approaches to the substantiation of unified (complex) norms in hygiene. The author discusses the determination of biological equivalence (isoeffectiveness) of concentrations of chemical substances in different environments on the basis of investigation of the relationship "concentration (dose) - time" as one of the possible methods of assessing the character of a complex action of these substances and one of the approaches to unified hygienic norm-setting.
Keywords: Environmental Pollution; Environmental Health; látky znečišťující vzduch v pracovním prostředí; Hygiene; Water Pollution, Chemical; Air Pollutants, Occupational; hygiena; znečištění životního prostředí; environmentální zdraví; kontaminace potravin; Food Contamination; chemické znečištění vody